The employment impact of China's WTO accession - Bhalla, A. S.; Qiu, Shufang (RoutledgeCurzon studies on the Chinese economy, 2004)
The book explores the macroeconomic and sectoral employment implications (in agriculture, industry and services) of China's World Trade Organisation accession.